Clarifying Deeper Psychological Characteristics of Hikikomori Using the Rorschach Comprehensive System: A Pilot Case–Control Study - Katsuki, Ryoko; Inoue, Ayako; Indias, Sílvia; Kurahara, Keita; Kuwano, Nobuki; Funatsu, Fumika; Kubo, Hiroaki; Kanba, Shigenobu; Kato, Takahiro A. (Frontiers in Psychiatry, 2019)
Hikikomori, a form of severe social withdrawal more than 6 months, has increasingly become a crucial issue especially among adolescents. Loneliness, avoidant personality, Japanese culture-related attachment style (“amae”), and difficulty in expressing emotions are suggested to be related to hikikomori. However, deeper psychological aspects have not been well clarified. The Rorschach test is one of the most popular psychological assessment tools to evaluate deeper personality traits. The Rorschach Comprehensive system (CS) has been established as the most reliable scoring method. Until now, no CS research has been conducted focusing on hikikomori. Therefore, we herein conducted a pilot case-control study using CS in clinical cases with and without hikikomori condition. Participants were recruited from the Mood Disorder/Hikikomori Clinic at Kyushu University Hospital. 22 patients with hikikomori (HK patients) and 18 patients without hikikomori (non-HK patients) participated in the present study. All the 40 participants conducted the self-report SCID-II personality questionnaire and CS. Regarding the SCID-II personality questionnaire, various personality traits including passive aggressive trait were significantly higher in HK patients. Among CS variables, HK patients showed higher scores on FC (Form Color) and SumT (total number of texture-related responses). In addition, frequency of SumT was higher in HK patients. The present results suggest that persons with hikikomori are more likely to express emotions indirectly and expect others to presume their feelings and thoughts. Persons with hikikomori may also have difficulty in becoming independent emotionally from primitive dependence and attachment on significant others. Further investigations with larger samples are warranted for validation.